(Di-tert-butylphosphanyl)bis(diphenylphosphanyl)phosphane - Wisniewska, Aleksandra (International Union of Crystallography, 2008)
The title phosphane, C(32)H(38)P(4) or (Ph(2)P)(2)P(P(t)Bu(2)), has a P atom that is linked to another three P atoms in a pyramidal configuration; the P—P distances in the range 2.2231 (7)–2.2446 (7) Å indicate that the P—P bonds are single bonds.